(untitled) (Revista de Investigación Intercultural ASAMPITAKOYETE, 2025)
Competency-based curriculum design in higher education has currently gained relevance in vocational training as a productive technique due to the urgent need to prepare citizens capable of facing the challenges of a globalized world. In this context, training modules become a transcendental didactic strategy for organizing learning around observable, relevant, and contextualized outcomes. However, in multicultural societies such as ours, it is essential to incorporate an intercultural approach in curriculum design and training modules to ensure their social relevance, equity, and recognition of the cultural diversity of the country and the region. This article reviews the literature on the design of training modules from a competency-based curriculum approach, emphasizing the contributions and challenges of the intercultural approach.